Development of Computer-Based E-Modules Using Flip Builder as a learning Resource in Social Studies Learning - Putri, Erika; Sudrajat , Sudrajat; Agustinova , Danu Eko (Universitas Muhammadiyah Sidoarjo, 2026)
The rapid development of information and communication technology and post-pandemic digital transformation have increased the demand for adaptive learning resources in Social Studies education. At SMP Negeri 1 Karangmojo, learning practices remained teacher-centered and dependent on textbooks despite available digital infrastructure, revealing limited integration of technology-based materials. This study aims to develop a computer-based e-module assisted by Flip Builder and to examine its feasibility using a Research and Development approach with the ADDIE model. Validation results showed Very Good categories from material experts (4.3), media experts (4.83), teacher readability tests (4.57), and student responses (4.68), indicating that the e-module meets eligibility standards. The developed e-module offers a systematically designed digital learning resource aligned with post-pandemic and 21st-century learning needs and can serve as an alternative resource to support student-centered and independent learning in junior high school Social Studies. Highlights: Multi-stage validation confirmed high eligibility across material, media, readability, and learner appraisal criteria. Systematic ADDIE procedures produced a structured digital resource aligned with curriculum competencies. Learner appraisal indicated strong acceptance regarding clarity, visual presentation, and instructional organization. Keywords: E-Module, Flip Builder, Social Studies, Learning Resources, ADDIE